Effectiveness of Rhizospheric Bacteria Microcapsules Addition on The Growth of Cocoa Leaves (Theobroma cacao L.) - Refnizuida, Refnizuida; Situmorang, Hadomuan; Hakim, Tharmizi; Ramadhani, Elrisa (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2023)
Cocoa (Theobroma cacao L.) is one of the main plantation commodities which plays an important role in the Indonesian economy, and 3rd ranked in the world for cocoa producers. One effort to increase cocoa productivity was the use of biological fertilizer. The aim of this research was to determine the effect of using rhizosphere bacterial microcapsules as biofertilizer on the vegetative growth of cocoa leaves. The research design used was a Completely Randomized Design, with two factors, the first was immersion the cocoa beans using a rhizosphere bacterial suspension consisting of A0=0 hours; A1= 8 hours; A2=16 hours and A3=32 hours and the second factor is the addition of microcapsules consisting of C0=0 gram( g ); C1=10gr, C2=20gr, C3=30gr. Combination The treatment was repeated twice so that 32 plants were obtained. For the parameter of observing the number of leaves, the best results were shown in the 8 hour immersion treatment with an average number of leaves of 12.63, followed by the treatment of giving 20 grams of capsules with an average number of leaves of 11.75. The lowest number of leaves was shown in the 16-hour and 32-hour immersion treatments at 10.75. Meanwhile, for the observation parameters of leaf area, the best results were shown in the 32 hour immersion treatment with an average leaf area of 73.49 cm 2 and the lowest results were shown in the non-immersion treatment with an average leaf area of 59.88 cm 2 . The results of the analysis of variance showed that all treatments had no significant effect